Direct growth of patterned graphene based on metal proximity catalytic mechanism - Zhihao Ye; Kun Xu; Qianqian Li; Siyuan Lu; Hao Wang; Junxian Zhao; Leiming Chen; Fanguang Zeng; Pei Ding; Ximin Tian; Yinxiao Du (Journal of Experimental Nanoscience)
In graphene electronics applications, in order to obtain the size and pattern required for the device, it is often necessary to photolithography the graphene after growth, resulting in contamination of graphene by the photoresist which have doping effect. Therefore, in order to avoid this effect, this article focused on directly grown patterned graphene. Based on atmospheric pressure chemical vapour deposition (APCVD) technology, patterned graphene was successfully grown on SiO2/Si by metal proximity catalytic effect. The patterned graphene was characterized by Raman spectroscopy and optical microscope. The effects of parameters such as gas flow, growth temperature, and growth time on the growth of patterned graphene were explored, and the best results were obtained. Metal copper and cobalt thin films were used for assisted catalysis, respectively, and the mechanism of metal proximity catalysis was explored. The experimental results showed that proximity catalysis is a catalytic growth mechanism based on surface diffusion. The growth method avoids using photolithography to make patterns, and can grow patterned graphene on insulating substrates or semiconductors in one step, which is of great significance for making patterned graphene and applying them to semiconductor devices.